2013
DOI: 10.1593/neo.121536
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of HGF Expression by ΔEGFR-Mediated c-Met Activation in Glioblastoma Cells

Abstract: The hepatocyte growth factor receptor (c-Met) and a constitutively active mutant of the epidermal growth factor receptor (ΔEGFR/EGFRvIII) are frequently overexpressed in glioblastoma (GBM) and promote tumorigenesis. The mechanisms underlying elevated hepatocyte growth factor (HGF) production in GBM are not understood. We found higher, coordinated mRNA expression levels of HGF and c-Met in mesenchymal (Mes) GBMs, a subtype associated with poor treatment response and shorter overall survival. In an HGF/c-Met-dep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 45 publications
1
25
0
Order By: Relevance
“…These results confirm a key role of c-Met in GBM progression. 29,[48][49][50][51] The lack of regulation of PY142 b-catenin by a c-Met inhibitor does not allow us to conclude if c-Met is phosphorylating this b-catenin site in GBM cells and rather suggests the involvement of other kinases. The proteolytic processing of c-Met is well described and nuclear c-Met has been linked to invasive cancers.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…These results confirm a key role of c-Met in GBM progression. 29,[48][49][50][51] The lack of regulation of PY142 b-catenin by a c-Met inhibitor does not allow us to conclude if c-Met is phosphorylating this b-catenin site in GBM cells and rather suggests the involvement of other kinases. The proteolytic processing of c-Met is well described and nuclear c-Met has been linked to invasive cancers.…”
Section: Resultsmentioning
confidence: 97%
“…22,23 Crosstalk between EGFR, c-Met and Wnt/b-catenin is well documented in cancer cells, thereby linking b-catenin signaling and cell migration induced by growth factors. [24][25][26][27][28][29] Thus, stimulation of epithelial cells with EGF or HGF through the phosphorylation of cell adhesion proteins diminishes cell adhesion while promoting epithelial-mesenchymal transition (EMT). Phosphorylation of Y142 b-catenin by c-Met affects b-catenin interaction with a-catenin 30 and promotes a b-catenin switch from adhesive to transcriptional functions that facilitates promigratory phenotypes.…”
Section: Introductionmentioning
confidence: 99%
“…EGFR is increasingly seen as an important STAT3 activator in GBM. For example, EGFRvIII (a constitutively active mutant missing exons 2–7) cooperates with wild-type EGFR to cause hyperactivation of STAT3 and STAT5—but not Akt or ERK—in GBM [89], and STAT3-mediated coordination between EGFRvIII and c-MET has also been described [90]. (Of note, however, is the recent observation that EGFR varieties are rarely coexpressed at the single cell level in GBM [24]. )…”
Section: Jak/stat3 In Gbmmentioning
confidence: 99%
“…Thus, when antiangiogenic therapy is applied to GBM, MET becomes hyperactivated, and indeed, inhibition of VEGF and MET effectively reduced invasive capacity of GBM tumors while improving survival [109]. As previously mentioned, MET is capable of driving STAT3 activation [90]. In bevacizumab-resistant GBM models, MET is upregulated, and p-Tyr705-STAT3 levels are increased twofold in bevacizumab resistant versus non-resistant GBM [110].…”
Section: Advances In Preclinical Studies Of Jak/stat3 In Gbmmentioning
confidence: 99%
“…9 A number of studies have reported a pro-oncogenic role of Met in glioma and that inhibition of Met is effective in inhibiting glioma growth in preclinical models. 1012 Transactivation of Met by EGFR signaling has been reported for EGFRwt as well as EGFRvIII in GBMs and other cancers. 13,14 Phosphorylation of Y1234 is required for Met activity and is particularly responsive to the presence of EGFRvIII.…”
Section: Introductionmentioning
confidence: 99%